Selective Catalytic Hydrocarboxylation and Deuterocarboxylation of Allyl Cyanide to Cyanobutanoic Acids with Monodentate and Bidentate Phosphines. Issue 6 (20th February 2017) - Vallcorba, Oriol; Polo, Alfonso; Real, Julio
Abstract: The hydrocarboxylation of allyl cyanide with monodentate phosphine systems (Pd/triphenylphosphine and protic acid cocatalyst) gave branched 3‐cyano‐2‐methylpropanoic acid chemo‐ and regioselectively, whereas with bidentate systems (Pd/bis[(2‐diphenylphosphino)phenyl] ether and protic acid cocatalyst) it gave linear 4‐cyanobutanoic acid chemo‐ and regioselectively. 3‐Cyano‐2‐methylpropanoic acid and 4‐cyanobutanoic acid were isolated in high yields as carboxylic acids and purified as benzyl esters. No isomerization of allyl cyanide to crotononitrile or its carbonylated derivatives was observed in any case. In parallel experiments, deuterocarboxylation under the same conditions gave the corresponding deuterated products, which were analyzed by MS and 2 H NMR spectroscopy: only d0, d1, and d2 products were detected. Deuterium entered the β and γ‐CN positions of the products but never the α position. Abstract : One bite or two? Allyl cyanide is converted catalytically to 4‐cyanobutanoic acid and 3‐cyano‐2‐methyl propanoic acid selectively. Deuterium labeling (MS, 2 H NMR spectroscopy) gave direct information on the intermediates involved in the process.